Defatted hickory meal hydrolysate’s impact on memory impairment induced by D-galactose in mice - Fanping Qin; Ruiling Liu; Qi Kong; Hangjun Chen; Xiangjun Fang; Huizhi Chen; Weijie Wu; Haiyan Gao (Food Science and Human Wellness)
Defatted hickory meal (DHM), a by-product of hickory oil production, is a protein source rich in essential amino acids. In this study, the functional properties of DHM hydrolysate (DHMH) were assessed using in vitro and in vivo assays in context to its antioxidant and memory-enhancing effects. To induce memory impairment, D-galactose (D-gal) was administered to mice at a dose of 120 mg/kg body weight per day, and DHMH was orally administered at doses of 300, 600, and 1000 mg/kg body weight per day for 8 weeks. DHMH treatment led to improved memory performance in D-gal-induced memory-impaired mice, as observed in the Morris water maze test. Furthermore, DHMH mitigated the accumulation of amyloid β1-42 triggered by D-gal exposure. Notably, high-dose DHMH significantly reduced the elevation of pro-inflammatory markers, including tumor necrosis factor alpha, interleukin 1β, and interleukin 6. Additionally, DHMH prevented the decline in total superoxide dismutase activity, glutathione peroxidase activity, and glutathione levels, while reducing malondialdehyde content in D-gal-induced mice, indicative of its antioxidant properties. Moreover, DHMH treatment effectively prevented histological alterations in neurons within the hippocampal CA1 area induced by D-gal. Collectively, our findings suggest that DHMH may counteract memory dysfunctions resulting from oxidative stress injury in the brain, positioning it as a potential candidate for use as a functional food.